The Effectiveness Of Metacognitive Instruction To Develop Listening Ability Of Students Of SMA Al Husain Yerr XI. - Dewi Nila Ainul Yaqin (PBI 14 UMY 001, 2014)
This study aims to reveal 1) the effectiveness of metacognitive instruction as a medium of learning listening skills; 2) The difference in listening ability between the experimental group who was taught using metacognitive instruction and the control who was taught without metacognitive instruction. This research was an experimental design with Nonequivalent Control Group design. The variables in this study included one independent variable that is metacognitive instruction and dependent variable, in this case listening skills. The population of this research is class XI SMA Al-Husain. The samples were determined using purposive sampling which included 21 students. Data were collected using tests to measure the listening skills before and after the treatment. The validity of the instruments in this study used expert judgment. The results of this study indicated that metacognitive instruction is an effective medium for teaching listening skills in grade XI class B SMA Al Husain Magelang. It is indicated in the posttest scores where in the experimental group, the pretest and posttest score show significant development. On the contrary the participants in the control group did not show any improvement. Thus, metacognitive instruction can be used to improve students’ listening skill. Keywords: effectiveness, metacognitiveinstruction, listening skills